2017
DOI: 10.4172/2324-8661.1000178
|View full text |Cite
|
Sign up to set email alerts
|

The Persian Gulf is Part of the Habitual Range of the Arabian Sea Humpback Whale Population

Abstract: The humpback whale has long been considered a rare straggler into the Persian Gulf, however new evidence contradicts this concept. We here critically review published and new records for Megaptera novaeangliae occurrence in the Gulf for the period 1883-2017. Of eight authenticated records (6 specimens, 2 live-sightings), seven are contemporary cases while one is a mid-Holocene specimen from UAE. An additional four are possible but unsubstantiated reports. Four regional, current, range states are confirmed, i.e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…The unique sighting of Arabian humpback whales reported at about 700 m from Dubai shores, has been the first sighting of a mother and calf recorded in the Gulf. This reinforced the evidence recently reported that the Gulf was once the natural habitat range for this endangered population (Dakhteh et al, 2017), estimated at only 82 individuals (Baldwin et al, 2013). Identified as the only humpback whale population that does not undertake seasonal migrations, this unusual behavior further limits the chance of population recovery (Pomilla et al, 2014).…”
Section: Discussionsupporting
confidence: 85%
“…The unique sighting of Arabian humpback whales reported at about 700 m from Dubai shores, has been the first sighting of a mother and calf recorded in the Gulf. This reinforced the evidence recently reported that the Gulf was once the natural habitat range for this endangered population (Dakhteh et al, 2017), estimated at only 82 individuals (Baldwin et al, 2013). Identified as the only humpback whale population that does not undertake seasonal migrations, this unusual behavior further limits the chance of population recovery (Pomilla et al, 2014).…”
Section: Discussionsupporting
confidence: 85%
“…All of the whales and many of the dolphins are endangered animals. Threats to whales are widespread and include fishery entanglements (Moazzam & Nawaz, 2014), ship strikes and pollution (Dakhteh et al, 2017). Owfi et al (2016) stated that the largest threat to marine mammals in Iran is incidental capture in fishing gears, where six bycaught finless porpoises were recorded and it is well known that this species may be particularly vulnerable to incidental mortality caused by gillnets.…”
Section: Threats Of Marine Mammals In the Arabian Gulf Cetaceansmentioning
confidence: 99%
“…Humpback whales perform long migrations from high latitude feeding grounds to their breeding and nursing areas in low latitudes [1,2,3], with the notable exception of the non-migrating Arabian Sea population that remains year-round in the Arabian Sea and Persian Gulf [3,4]. However the paradigm of this long migration for feeding or breeding strategies is under discussion as an increasing number of studies show humpback whales feeding in formerly unrecognized mid or low latitudes [5,6,7,8,9,10].…”
mentioning
confidence: 99%